XIX in MMI in HISK. - Swinnen, Johan; Doove, Edith; Mellaerts, Betty; Pas, Johan; Ruyters, Marc; Elias, Willem (Antwerpen : Willem Elias, 2001)
Aertsen, Gert ; Bogaert, Wina ; Claeyé, Catherine ; Coolen, Caroline ; Denys, Ward ; Dockx, Nico ; Jessen, Joseph ; Maes, Ives ; Naveau, Nadia ; Paelinck, Lieven ; Redjaian, Haleh ; Renneboog, Lucie ; Ruiz Ruiz, José Maria ; Sosnowksi, Marika ; Tosseyn, Tom ; van Haren Noman, Ruth ; Vermeersch, Pieter ; Visic, Loreta ; Volders, Jethro
Met essay van Willem Elias 'Kleine filosofie van de nieuwe media'
Tentoonstelling laureaten 2001, HISK, Antwerpen, 1 juni - 16 juni 2001
boek